Ion Diffusion Behavior between Fracturing Water and Shale and Its Potential Influence on Production - Yinghao Shen; Zhaopeng Zhu; Peng Shi; Hongkui Ge; Zhihui Yang (Journal of Chemistry)
Water imbibition, conductivity measurements, and ion identification were performed to investigate ion diffusion behavior between slick water and shale for large-scale hydraulic fracturing. The results indicated that there was strong ion exchange between water and shale. The ion concentration in water increases with fracture complexity and is dependent on the salinity of fracturing fluids. This implies that fracturing effects could be forecast from flow-back fluid ion concentrations after large-scale slick water fracturing. Higher levels of ion diffusion imply the presence of larger fracturing areas and higher level of fracture density for a similar reservoir. The mechanism of ion diffusion and the corresponding effects on IOR (increased oil recovery) based on a field example are discussed.